Intellectual Resources and Operational Cost-effectiveness in Banks: An Empirical Analysis from Vietnam - Chi Huu Lu (Asian Academy of Management Journal of Accounting and Finance, 2024)
The central role of intellectual resources in business operations of banks has been recognised and unveiled in the extant literature in recent times. However, it seems to be a virtual absence of studies on the impacts of these resources on the efficiency of operational costs in the banking industry, especially in developing markets. Hence, this research aims to fulfill this research gap by employing VAIC model and investigating its role in operating cost management of 26 local banks in Vietnam during the 2006–2020 period. After performing various econometrics methods and robustness tests, the continuing evidence demonstrates that the effectiveness of operating expenditures may be enhanced significantly by relying specially on intellectual capital. Additionally, human and structural capitals are two ingredients of VAIC that can assist banks in managing operating costs more effectively. By contrast, an increase in capital employed – the third ingredient – may accelerate costs related to operational business. Taken together, it is expected that the empirical findings can provide the helpful guidance for managers and decision-makers in banks to optimise the cost-effectiveness in daily business operations and pay new paths for academicians to dig more into the role of knowledge-based management in coming future.